Verbal explication of (intra-)inter-event causal relations in the story-telling: Comparative study of primary language-impaired and typically-developed pre-schoolers - Kornev, Aleksandr N.; Balčiūnienė, Ingrida (Focus on events and narratives in language, psychology, social and medical practice, 2020)
The current study aimed at evaluating children’s ability to explicate verbally the cause-and-effect relations between the events, sequentially organized actions of the characters and their goal-outcome connections. The subjects of our study, i.e. 12 typically-developing (TD) and 12 primarily language-impaired (PLI) Russian preschoolers (mean age 76 months) were asked to tell a story according to a picture sequence. A dual analysis of the verbal explication of causal relations was carried out: 1) during the semantic quantitative analysis of narrative coherence, two types of relations between the events or the characters’ actions were estimated: (a) verbally explicated causal relations and (b) semantic relations explicated by sequencing the actions following the “post hoc ergo propter hoc” presupposition (Sanders, 2005); 2) an analysis of the linguistic causal relations was based on a distribution of causal vs. non-causal connectives, such as conjunctions and discourse markers, in the narratives. The statistical analysis revealed significantly infrequent use of causal connectives in the PLI children if compared to the TD peers. As for the semantic relations, the score for the causal relation index was significantly lower in the PLI children than in the TD peers, contrary to the score for the semantic relation index. Among the linguistic devices used for an explication for causal relations, however, only the percentage of causal conjunctions was significant between the groups.